Effect of Processing Time on Recovery and Quality of Essential Oil from Patchouli (Pogostemon cablin Benth.) - Parganiha, D.; Patel, S.; Paikra, C. K.; Sahu, P. (International Journal of Economic Plants, 2018)
Patchouli (Pogostemon cablin) is fragrant herb produce essential oil, known as patchouli oil having high economic importance. Patchouli oil is widely used in food, pharmaceutical and cosmetic industries. Global demand is very high for Patchouli oil as compare to its production. Patchouli oil extraction is still new but has large market demand due to therapeutic and healing properties of oil. In this study an effort to increase the recovery of patchouli oil by standardizing the extraction process was performed. Drying of herbage before extraction was done in oven at 50 oC. Recovery of patchouli oil at different intervals of processing time viz., 4, 5, 6, 7 and 8 hours at 15% moisture was analyzed. It was observed that the oil recovery increased from 1.8 to 2.43% (w/w) as processing time increased from 4 to 8 hours. The patchouli oil samples extracted during the study were also analyzed for its physico-chemical quality. All the extracted oil samples have shown the values of physico-chemical parametre in the satndard permissible range of patchouli oil except long extraction time (after 7 hours), due to which acid value of oil exceds the permissible limit. Hence, from the above work it may be concluded that the extraction of essential oil should be carried out at combination of 15% moisture (db) and 7 hours of processing time intervals for better recovery and quality of oil.